Law of remedies a European perspective - Hofmann, Franz 1981-; Kurz, Franziska (Intersentia, 2019)
With the increasing importance of the concept of remedies in European private law, this book focuses on remedies as a distinctive and novel field of European legal research. It considers the common law tradition (England and Wales), as well as the civil law viewpoint (on the example of Germany), making the case for a European law of remedies. It is argued that 'remedies' are an enforcement tool influencing the scope of substantive rights. In doing so, the book analyses different mechanisms of enforcement, including the debate on private versus public enforcement as well as the perspective of criminal law. The enforcement of rights is understood as an intradisciplinary task. Remedial law is, however, distinct from procedural law, as well as from substantive law in a narrow sense. Subsequent to defining the scope of a law of remedies, this book analyses several underlying principles and common themes.